1998
DOI: 10.1037/0022-006x.66.2.411
|View full text |Cite
|
Sign up to set email alerts
|

The use of religious coping during stressful life events: Main effects, moderation, and mediation.

Abstract: The effects of religious coping, the potential moderation of such effects by religious affiliation (i.e., Catholic, Protestant), and the potential mediation of such effects by various factors (i.e., cognitive restructuring, social support, perceived control) were investigated in patients and significant others coping with the stress of kidney transplant surgery. At 3 and 12 months after transplantation, results showed that the use of religious coping was generally associated with better adjustment both concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
223
5
14

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(254 citation statements)
references
References 38 publications
12
223
5
14
Order By: Relevance
“…It was noted by Pargament et al (2004) that methods of positive religious coping, such as the search for religious support among elderly patients, were linked to improvements in health. The significance of religious coping was also elucidated by Tix and Frazier (1998) who found that religious coping was associated with improved adjustment to the stress of kidney transplant surgery.…”
Section: Religion As a Means Of Resilience And Copingmentioning
confidence: 99%
“…It was noted by Pargament et al (2004) that methods of positive religious coping, such as the search for religious support among elderly patients, were linked to improvements in health. The significance of religious coping was also elucidated by Tix and Frazier (1998) who found that religious coping was associated with improved adjustment to the stress of kidney transplant surgery.…”
Section: Religion As a Means Of Resilience And Copingmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46] Most of these studies showed an association between religiosity and wellbeing even after controlling for age, gender and socioeconomic status. Some studies have shown that the positive impact of religious involvement on well-being is more robust among the elderly, disabled, and medically ill people.…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…Epidemiological studies indicate people frequently rely on religion to cope with life stresses, with meta-analyses demonstrating positive impacts of religious coping on wellbeing (Ano & Vasconcelles, 2005;Harrison, Koenig, Hays, Eme-Akwari, & Pargament, 2001). Additionally, a smaller number of studies has found religious coping to moderate the relationship between stress and wellbeing, providing support for the buffering hypothesis (Aydin, Fischer, & Frey, 2010;Carpenter, Laney, & Mezulis, 2012;Fernandez & Loukas, 2014;Tix & Frazier, 1998). These findings elucidate the two mechanisms by which coping can affect adaptation outcomes (Ensel & Lin, 1991).…”
Section: The Role Of Religion In Coping With Stressmentioning
confidence: 92%
“…This line of research indicates that disempowered and deprived groups, including women and ethnic minorities, not only tend to use religious coping more often, but also derive a greater sense of efficacy from it (Harrison et al, 2001). In addition, religious coping has been shown to be utilized more heavily at times when situations are appraised as uncontrollable or perceived as greatly exceeding one's resources (Pargament, 1997;Tix & Frazier, 1998), thus providing an outlet for those at a social disadvantage and with limited access to external resources.…”
Section: The Role Of Religion In Coping With Stressmentioning
confidence: 99%